Implante de tubo traqueal : modelo experimental para estudo das alterações cárdio-respiratórias observadas na hipertensão pulmonar - Waichert Júnior, Élio (2006)
The aims of this study were to evaluate cardiovascular, respiratory and gasometric changes in rats submitted to tracheal tube implantation and limitation of the chest. Under anesthesia, Wistar rats (240 – 270 g) were submitted to implantation of the one polyethylene tube (PE-90 with length of 8 mm) into the trachea for a period of 8 days and implantation of the rubber jacket around the chest to permit a certain limitation of expansion (JK+TTc group). Sham (ficticia surgery), TTc (rats submitted only to implant of PE-90 into the trachea) and JK-Sham (rats submitted only of the rubber jacket) animals were used as control. Are day before the recording period, under anesthesia, these animals had the femoral artery and vein canulated to permit cardiovascular, respiratory and gasometric recordings and drugs administration, respectively. Results showed a significant increasing in the basal heart rate (HR) in rats JK+TTc, as well as in the basal levels of the mean arterial pressure (MAP), systolic arterial pressure (SAP) and diastolic arterial pressure (DAP). In relation to respiratory parameters, these animals present a significant increasing in the respiratory frequency (RF), tidal volume (TV) and pulmonary ventilation (PV). In relation to the gasometric parameters, we observed a decrease of the partial pressure of oxygen (PpO2), increase of the partial pressure of carbon dioxide (PpCO2), reduction in the percentage of hemoglobin saturation and acidosis. It was also observed that these animals had a significant increase in the right ventricular weight, while the same it was not observed in relation to the left ventricle. In relation to cardiovascular reflexes, we observed that the animals JK+TTc present: a reduction in the baroreflex gain, an increase of chemoreflex pressor response in the dose of 10 and 20 µg/0.05 ml and an attenuation of the bradycardic response in dose of 40 and 80 µg/0.05 ml. In relation to Bezold-Jarisch reflex, we observed a significant attenuation of the hypotension and bradycardic responses. The evaluation of the autonomic components showed an increase in the sympathetic component and a reduction in the parasympathetic component. The role of the peripheral chemoreceptors was evaluated in 2 separated groups of animals: JK+TTc 1 day (animals submitted to tracheal tube implant plus chest jacket and were evaluated 1 day after the implantation) and JK+TTc PCR (animals submitted to tracheal tube implant plus chest jacket and removal of the peripheral chemoreceptors). We observed that the animals of the JK+TTc PCR grops presented RF and PV values significantly smaller than JK+TTc 1 day, while it was not observed a significant changes in TV between these groups. The animals of JK+TTc PCR present a significant reduction in the HR in relation the group JK+TTc 1 day, while a significant changes in MAP, SAP and DAP values were not observed among groups. The group JK+TTc PCR presented a significant decrease of the PpO2, pH and % of O2 Hbsaturation values and a significant increase in the PpCO2 and [H+] values in relation to the JK+TTc 1 day group. Our results suggest that the technique of tracheal tube implant plus chest limitation produces an important picture of pulmonary hypertension associated to a chronic hypoxemia and a several important cardiovascular and respiratory changes. The changes cited above and the possible repercussion result from the increasing air flow resistance, as well as pulmonary blood flow, constitute an important model for the study of pulmonary hypertension and also of the right ventricular hypertrophy (Cor pulmonale), as observed in these animals. These results also showed that the mechanisms of the cardiovascular regulation are significantly changed in the pulmonary hypertension, being the chemoreflex activation, a fundamental key the animals survival. We also observed that in this model of pulmonary hypertension, several cardio-respiratory parameters were already altered changed in the first day after the implants, whose alterations seems to be mediated mainly by peripheral chemoreceptors.